CRONO: a fast and reconfigurable macro X‐ray fluorescence scanner for in‐situ investigations of polychrome surfaces. (8th February 2017) - Alberti, R.; Frizzi, T.; Bombelli, L.; Gironda, M.; Aresi, N.; Rosi, F.; Miliani, C.; Tranquilli, G.; Talarico, F.; Cartechini, L.
Abstract : CRONO is a new portable and easy reconfigurable macro X‐ray fluorescence scanner based on the energy dispersive X‐ray fluorescence technique, which has been specifically designed for in‐situ, fast, and non‐invasive elemental mapping of polychrome surfaces. The main components are fully integrated into the detection head which includes an X‐ray tube, a large area silicon drift detector, a microscope camera, two pointing lasers, a Helium gas purging set, and fast acquisition electronics. This very compact detection head is mounted on motorized stages (with a linear speed up to 45 mm/s) that allow the scanning of areas up to 450 × 600 mm 2 . Three collimators (0.5, 1, and 2‐mm diameter) are software selectable to obtain different spot sizes on the sample. The typical measurement time for the full scanned area ranges from 1 h with the 2‐mm collimator to about 9 h with the 0.5‐mm collimator using a dwell time of 30 ms. Technical details and achievable performances of the instrument are presented and discussed along with an example of application which illustrates the value of the developed instrument in the investigation of paintings. Copyright © 2017 John Wiley & Sons, Ltd.